Atomically Thin, Ionic–Covalent Organic Nanosheets for Stable, High‐Performance Carbon Dioxide Electroreduction. Issue 42 (14th September 2022) - Song, Yun; Zhang, Jun‐Jie; Dou, Yubing; Zhu, Zhaohua; Su, Jianjun; Huang, Libei; Guo, Weihua; Cao, Xiaohu; Cheng, Le; Zhu, Zonglong; Zhang, Zhenhua; Zhong, Xiaoyan; et al.
Abstract: The incorporation of charged functional groups is effective to modulate the activity of molecular complexes for the CO2 reduction reaction (CO2 RR), yet long‐term heterogeneous electrolysis is often hampered by catalyst leaching. Herein, an electrocatalyst of atomically thin, cobalt‐porphyrin‐based, ionic–covalent organic nanosheets (CoTAP‐iCONs) is synthesized via a post‐synthetic modification strategy for high‐performance CO2 ‐to‐CO conversion. The cationic quaternary ammonium groups not only enable the formation of monolayer nanosheets due to steric hindrance and electrostatic repulsion, but also facilitate the formation of a *COOH intermediate, as suggested by theoretical calculations. Consequently, CoTAP‐iCONs exhibit higher CO2 RR activity than other cobalt‐porphyrin‐based structures: an 870% and 480% improvement of CO current densities compared to the monomer and neutral nanosheets, respectively. Additionally, the iCONs structure can accommodate the cationic moieties. In a flow cell, CoTAP‐iCONs attain a very small onset overpotential of 40 mV and a stable total current density of 212 mA cm –2 with CO Faradaic efficiency of >95% at −0.6 V for 11 h. Further coupling the flow electrolyzer with commercial solar cells yields a solar‐to‐CO conversion efficiency of 13.89%. This work indicates that atom‐thin, ionic nanosheets represent a promising structure for achieving both tailored activity and high stability. Abstract : The methylation of cobalt‐porphyrin‐based covalent organic nanosheets successfully introduces quaternary ammonium groups into the framework, and resolves the leaching problem of ionic catalysts. The steric hindrance and electrostatic repulsion effect of ammonium groups benefit the formation of monolayer nanosheets and the exposure of active sites. Meanwhile, the cationic skeleton decreases the energy barrier for the *COOH formation and facilitates electrocatalytic CO2 ‐to‐CO conversion.